A Realization of Hom-Lie Algebras by Iso-Deformed Commutator Bracket - Xiuxian Li (Abstract and Applied Analysis)
We construct classical Iso-Lie and Iso-Hom-Lie algebras in by twisted commutator bracket through Iso-deformation. We prove that they are simple. Their Iso-automorphisms and isotopies are also presented.